Implementasi Augmented Reality pada Mata Pelajaran Komputer dan Jaringan Dasar di SMK Nufa Citra Mandiri Berbasis Android - Bobi Agustian; Muhamad Yasser Arafat (Jurnal Informatika Universitas Pamulang, 2020)
In the process of teaching and learning activities in schools, there are still many that only use learning media in the form of books. This causes boredom in the learning process. Especially in basic computer and network subjects, where in this subject there is a lot of visual recognition and developing forms of technology. Good visual presentation is very important to support the learning process. Augmented Reality (AR) is a learning medium that is currently still being used in the teaching and learning process. AR is an application that combines the real world with the virtual world in two-dimensional or three-dimensional forms which are projected in a real environment at the same time. AR technology is very appropriate to be implemented to support the visualization process in learning activities, because it can present visualization in 3-dimensional form. So that the visualization is more interactive and more interesting. In the learning process at SMK Nufa Citra Mandir, they still rely on books only, especially in computer and basic network subjects which really need visualization of the devices discussed. The application of AR technology to basic computer and network subjects at SMK Nufa Citra Mandiri is expected to help in the learning process. In its development, the design method used is the Extreme Programming (XP). Purpose of this research is to create software with AR technology on Android platform, so that students can better understand and get to know computer tools and computer network devices contained in basic computer and network subjects.